Psychological Resilience and Organizational Commitment: Mediating Role of Job Satisfaction - Mehmet Doğan; Bülent Gürbüz; Tülay Avcı Taşkıran (Atatürk University, 2024)
This study examined the relationship between psychological resilience, job satisfaction, and organizational commitment. The study, which was conducted with the relational survey model, was attended by 204 women and 176 men, 380 people in total (MAge=37,87±7,88) working in the Directorate of Youth and Sports. Participants answered the personal information form, "The Brief Resilience Scale (BRS)", "Job Satisfaction Scale (JSS)" and "Organizational Commitment Scale (OCS)". After data collection, the basic assumptions of parametric tests were tested, and a model was created to examine the relationship between "BRS", "JSS" and "OCS" and the causal relationship between the latent variables was analyzed with the Structural Equation Model. The Pearson correlation analysis results showed significant positive correlations between the mean scores of "BRS", "JSS" and "OCS". When the goodness of fit values of the model were examined, it was found that all values were within acceptable limits. SEM results showed that psychological resilience had direct positive significant effects on job satisfaction (βBRS-JSS=0.22; p<0.01) and organizational commitment (βBRS-JSS=0.17; p<0.01), and job satisfaction had direct positive significant effects on organizational commitment (βJSS-OCS=0.48; p<0.01). Simultaneously, it was determined that job satisfaction had an indirect effect on the effect of psychological resilience on organizational commitment (βBRS-JSS-OCS=0.10; p<0.01). According to the results of the current research, psychological resilience and job satisfaction have a direct effect on organizational commitment, and job satisfaction has an indirect effect by assuming a partial mediating role in the relationship between psychological resilience and organizational commitment. Therefore, by increasing the levels of psychological resilience and job satisfaction of individuals, it may be possible to change their attitudes toward the organization and accordingly increase their organizational commitment levels.